Dossier: Escrituras de infancia La reescritura de La infancia en Los días ocultos de Luis Oyarzún1 - Lorena Amaro Castro (2018)
Philosopher Luis Oyarzún wrote two autobiographical novels that present the perception of a child from the province: La infancia (1940) (Childhood) and Los días ocultos (1955) (Hidden Days). Critics such as Roberto Hozven, Leonidas Morales and Olga Grau state that the second novel is a new version of the first one. This article compares both texts, seeking to elucidate and understand the differences between them and examining, in both cases, the extents to which they reveal a more mature writing, as well as the concerns of an author that until today holds a marginal place in the construction of a Chilean philosophical and literary canon